HUMANITIES PAPER: EPISTEMOLOGICAL AND HISTORICAL-CULTURAL PERSPECTIVE: ROUND TABLE DISCUSSION (PART 2) - Editorial Article (Высшее образование в России)
The round table discussion of the journal Vysshee obrazovanie v Rossii (Higher Education in Russia) took place on March 14, 2017 within the framework of Humanities Readings at Russian State University for the Humanities. The key theme - the model of the modern research journal in various aspects: philological (academic writing, IMRaD), philosophical (criteria of scholarly publication), historical and cultural, economical. The participants have touched upon such issues as interrelations between an author and an editor, types of peer review, the epistemological model of editor's activities, assessment of research activities, scientific communication. Special attention was paid to academic writing and suitability of IMRaD format for Humanities papers, scientometrics.